Genotoxicity evaluation of tobacco and nicotine delivery products: Part One. Mouse lymphoma assay. (October 2019) - Thorne, David; Leverette, Robert; Breheny, Damien; Lloyd, Mel; McEnaney, Stephen; Whitwell, James; Clements, Julie; Bombick, Betsy; Gaca, Marianna
Abstract: Conduct of the mouse lymphoma assay (MLA) is underpinned by Organisation for Economic Co-operation and Development (OECD) Test Guideline 490 and International Conference on Harmonisation S2(R1) guidance and is a recognised in vitro genotoxicity test battery assay. It has been used on a limited number of occasions for the assessment of some tobacco and nicotine products, such as e-cigarettes and tobacco heating products (THP). The aim of this study was to assess the suitability of the MLA for genotoxicity testing with a variety of tobacco and nicotine products. Total particulate matter (TPM) from a 3R4F cigarette was compared against a commercial electronic cigarette liquid (e-liquid), electronic cigarette (e-cigarette) aerosol matter captured from the same e-liquid, and TPM from a commercial THP. Treatment conditions included 3 h exposures with and without metabolic activation and a longer 24 h exposure without metabolic activation (-S9) at concentrations up to 500 μg/mL. Under all treatment conditions, 3R4F produced a clear positive response with regard to induction of mutation. In contrast, no marked induction of mutation was observed for the e-liquid, e-cigarette aerosol or THP. Additionally, data are presented as a function of nicotine equivalents for comparisons between these different tobacco products and test matrices. Highlights: Cigarette was compared against a commercial e-liquid, e-cigarette, a commercial THP. Data are presented as a function of nicotine equivalents for comparisons between different test matrices and products. This manuscript is Part One of a Two-Part series detailing the toxicological evaluation of the same test articles. Under all treatment conditions, 3R4F produced a clear positive response. In contrast, no marked induction of mutations was observed for e-liquid, e-cigarette aerosol or THP test articles.